Las lluvias intensas en Las Palmas de Gran Canaria el 21 de octubre de 2020 - Rodríguez Franco, Juán José (Revista Tiempo y Clima, 2021)
Las lluvias intensas en Las Palmas de Gran Canaria el 21 de octubre de 2020